Human Resource Development as a Strategy for Improving Employee Competencies in the Local Government Sector - Tri Sasti Rahmawati; Sri Wulandari (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
This study examines human resource development as a strategy for enhancing the competencies of employees within the local government environment, specifically at the Civil Service and Human Resource Development Agency (BKPSDM) of Kuningan regency. The study aims to analyze the implementation of human resource development, assess the competency levels of Civil Servants (ASN), and identify the supporting and inhibiting factors in the competency development process. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews and documentation, and were analyzed using Noe’s Human Resource Development Theory and wibowo’s Competency Theory. The finding indicates that the implementation of human resource development at BKPSDM Kuningan Regency has been carried out in accordance with applicable regulations and is based on a merit system and talent management. Competency development is conducted through various programs, including education and training, technical guidance, coaching, mentoring, and the utilization of a Learning Management System (LMS). The competency level of ASN is categorizes as good, as reflected in the Civil Servant Professionalism Index. However, the implementation still faces several challenges, such as limited budget, a shortage of instructors, and suboptimal participation of employees. On the other hand, the process is supported by the commitment of implementers, systematic planning, the application of a merit system, and the use of LMS as an efficiency strategy. Optimization efforts are carried out through strengthening talent management, developing an internal LMS, and establishing cooperation with other competency development institutions.